Deposition and Characterization of Cerium-Based Conversion Coating on HPDC Low Si Content Aluminum Alloy. Issue 9 (20th July 2017) - Eslami, Maryam; Fedel, Michele; Speranza, Giorgio; Deflorian, Flavio; Zanella, Caterina
Abstract : Cerium-based conversion coatings were deposited on high pressure die cast (HPDC) Al-Si alloys using an immersion method. Hydrogen peroxide and sodium chloride were added to the conversion solution to accelerate the coating formation and to understand its formation mechanism. These studies showed that the deposition of cerium hydroxide/oxide conversion layer starts from iron-rich intermetallic particles, which are located inside the eutectic region and then the coating growth continues to cover the entire alloy surface. This phenomenon passivates the active interfaces between iron-rich intermetallic particles and/or the eutectic silicon phase and the aluminum matrix, which are prone to localized corrosion in chloride ions containing environments. Accordingly, values of the total impedance in EIS measurements significantly increased for the treated substrates. Morphologies of the conversion coatings and the oxidation state of cerium compounds were found to be dependent on the composition of the solution and the presence of chloride ions and/or hydrogen peroxide. Aluminum alloy with higher silicon content showed a more active surface during immersion in the conversion solution. This makes it more difficult to be treated using aggressive conversion solutions.